Experimental Study on Damage and Degradation of Structure Plane in Rock Mass under Cyclic Shear Load - Rubao Hong; Wenbin Jian; Deng Zhang; Ruimin Chen (Geofluids)
By summarizing the generalized model of the structural plane in a rock mass under a cyclic shear load and influencing factors of dynamic mechanical properties of the structural plane, the mechanism of structural plane damage and degradation is discussed, and the evolution of damage to the structural plane is ascertained from cyclic shear tests by using structural planes with different undulating angles. Based on model tests and previous studies, nonlinear constitutive equations considering the effect of structural plane damage and degradation are presented. The effects of the initial undulating angle, amplitude of the cyclic shear load, and cycle times on the strength of the structural plane, as well as the degeneration process of structural plane stiffness under a cyclic shear load, are taken into consideration in the equations. The applicability of the above-mentioned constitutive equations is analyzed with a corresponding program compiled in the FISH language in the Universal Distinct Element Code (UDEC). The UDEC numerical simulation results are verified with ones from the model test. The achievements presented in this paper are of great significance to theoretical study of the mechanical behaviors of rock masses under cyclic shear loads and to project practice.